Expression of CD56 defines a distinct subgroup in childhood T-ALL with inferior outcome: Results of the ALL-BFM 2000 trial - Fuhrmann, Stephan; Kunz, Joachim; Kulozik, Andreas (British journal of haematology, 2018)
This study reports the prognostic impact of the expression of the natural killer cell marker CD56 in a large series of risk-adapted paediatric patients with T cell acute lymphoblastic leukaemia (T-ALL; n = 493) treated within the ALL-Berlin-Frankfurt-Münster (BFM) 2000 protocol. The immunophenotype was analysed centrally at diagnosis using flow cytometry and correlated with clinical parameters and outcome. CD56 expression was detected in 7·1% and early T-cell precursor (ETP) phenotype in 6·7% of all T-ALL patients. The percentage of ETP in the CD56+ T-ALL cohort was 4-fold higher than in the whole cohort. CD56+ T-ALL frequently expressed the progenitor marker CD34 and myeloid antigens CD13 and CD33. The 5-year event-free survival (EFS) rates for the European Group for the Immunological classification of Leukaemias/World Health Organization subgroups and the ETP phenotype were not statistically different. By contrast, patients with CD56 expression had a significantly reduced EFS (60 ± 8%) and overall survival (60 ± 8%) at 5 years, with a hazard ratio of 2·46 (P = 0·002) and 2·99 (P < 0·001), respectively. Moreover, CD56 expression in combination with the minimal residual disease (MRD)-based high risk assignment defined a population with a ‘very-high’ risk probability of relapse in the ALL-BFM 2000 trial. The CD56 marker has the potential to augment MRD-based risk stratification and may serve as a molecular target for antibody-based treatment strategies in childhood T-ALL.